Overoptimistic Entrepreneurs: Predicting Wellbeing Consequences of Self-Employment - Reto Odermatt; Nattavudh Powdthavee; Alois Stutzer (Institute of Labor Economics (IZA), 2017)
The formation of expectations is a fundamental part of the process when people decide about engaging in an entrepreneurial venture. We evaluate the accuracy of newly self-employed people's predictions of their overall future wellbeing. Based on individual panel data for Germany, we find that they are overly optimistic when we compare their predicted life satisfaction with their actual life satisfaction five years later on. This overoptimism also holds for those entrepreneurs who successfully remain in business for at least five years. A possible reason might be that they underestimate the heavy workload reflected in higher working hours than desired and the drop in leisure satisfaction.
Keywords: D83; D91; J20; I31; 330; adaptation; overoptimism; life satisfaction; projection bias; wellbeing; self-employed